Research on the Fatigue of Small Impulse Turbine Blade Based on the Numerical Simulation and Experimental Tests - Shijie Liu; Guozhu Liang; Jichao Liu; Yichuan Yang; Hui Wang (International Journal of Aerospace Engineering)
Reusable spacecraft is increasingly attracting researchers’ attention. However, the experimental investigations on the turbine blade of the rocket engine are rarely published. Thus, the fatigue of a small impulse rocket turbine blade is explored in the current work. First, the specimen and the electrode of electrical discharge machining are carefully designed. Then, the electrical discharge machining is used to machine the specimen. To study the fatigue properties, the finite element analyses are separately performed on the blade model and the specimen. Based on the numerical results, a fatigue test is carried out to reproduce the most vulnerable position. Finally, the microstructural structures of the specimen are detected using the scanning electron microscope (SEM). Results show that (1) different from the aviation field, the specimen is unable to be machined with the welding method because it destroys the crucial details and the mechanical properties; (2) the maximum plastic strain is present at the leading edge close to the hub, at which a 760 μm corner crack appears at the 10113th fatigue cycle. This work provides a feasible method of using the EDM process to machine specimen for the small impulse turbine blade.